The Uşaklı Höyük Survey Project (2008-2012) - Pecchioli, Franca; Mazzoni, Stefania (Studia Asiana, 2015)
This book presents the results of the survey conducted by the University of Florence, in the years 2008-2012, at the site and in the surrounding territory of Uşaklı Höyük on the central Anatolian plateau in Turkey. Geological, geomorphological, topographic and geophysical research have provided new information and data relating to the environment and the settlement landscape, as well as producing new maps of the area and indicating the presence of large buried buildings on the site. Analysis of the rich corpus of pottery collected from the surface indicates that the site and its territory were continuously settled from the late Early Bronze Age through the Iron Age and down to the Late Roman and Byzantine periods. A few fragments of cuneiform tablets with Hittite texts, a sealing with two impressions of a stamp seal, and pottery stamps illustrate the importance of Uşaklı Höyük and support the hypothesis of its identification with the town of Zippalanda, known from the Hittite sources as a seat of the cult of the Storm God.